2010
DOI: 10.1002/hyp.7721
|View full text |Cite
|
Sign up to set email alerts
|

Preferential flow paths through soil and rock and their association with landslides

Abstract: Abstract:This article discusses preferential flow paths through soil and rock and how these contribute to the style and timing of landslides. The importance of geological compartmentalization because of the presence of aquicludes such as weathered dykes and faults is emphasized as is channel flow through fracture networks and through natural pipes in soil-like material. Although piping is a contributing factor to some landslides, as generally recognized, it can also be a sign of inherent distress in a developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…Some studies have shown that preferential flow is one of the major mechanisms affecting the timing and location of landslides (Sharma and Nakagawa, 2010;Uchida, 2004;Verachtert et al, 2013). In hillslopes, preferential flow paths, such as macropores, soil pipes, and fissures, have been associated with slope stability (Hencher, 2010;McDonnell, 1990;Uchida et al, 2001;Krzeminska et al, 2012;Debieche et al, 2012). Besides the fact that internal erosion in preferential flow paths deteriorates the slope mass and reduces the soil shear strength, the occurrence of preferential flow can give rapid access to the deeper soil and groundwater system, reduce soil shear strength (due to pore pressure changes), and influence the timing and frequency of landslides (Wienhöfer et al, 2011;Uchida, 2004;Verachtert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that preferential flow is one of the major mechanisms affecting the timing and location of landslides (Sharma and Nakagawa, 2010;Uchida, 2004;Verachtert et al, 2013). In hillslopes, preferential flow paths, such as macropores, soil pipes, and fissures, have been associated with slope stability (Hencher, 2010;McDonnell, 1990;Uchida et al, 2001;Krzeminska et al, 2012;Debieche et al, 2012). Besides the fact that internal erosion in preferential flow paths deteriorates the slope mass and reduces the soil shear strength, the occurrence of preferential flow can give rapid access to the deeper soil and groundwater system, reduce soil shear strength (due to pore pressure changes), and influence the timing and frequency of landslides (Wienhöfer et al, 2011;Uchida, 2004;Verachtert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Parameter variability is often assessed by making small scale laboratory measurements of parameters such as cohesion and coefficient of friction but the resulting values may not be 10 directly applicable at the large scale because of the effects of spatial heterogeneities, and additional factors such as root strength (Christian et al, 1994;Rubio et al, 2004;Hall et al, 2004;Hürlimann et al, 2008;Hencher, 2010). Although spatial variability of soil properties has been recognised as an important source of epistemic uncertainty in the literature (e.g.…”
Section: Uncertainty Quantification In Landslide Hazard Estimationmentioning
confidence: 99%
“…require greater computational power and may still not represent the water flow processes adequately, such as the role of preferential flows and bedrock fracture systems in inducing conditions for failure (e.g Montgomery et al, 2009;Hencher, 2010;Beven, 2010;Beven and Germann, 2013). Even at sites where the costs of extensive field investigations can be justified, there is much that remains unknown about the subsurface including the detail of water flow pathways and knowledge of the hydro-mechanical behaviour of soils.…”
Section: Uncertainty Quantification In Landslide Hazard Estimationmentioning
confidence: 99%
“…It might take many iterative minor movements from extreme rainfall events before the controlling, wavy first order asperities (Patton and Deere 1970) are overridden and the slab detaches down slope as illustrated by the Leung King Estate, Hong Kong, case example presented below. The water flow through all joints is tortuous, channelised and localised (Kikuchi and Mito 1993;Hencher 2010) and this will be especially true of most sheeting joints with their rough and wavy surfaces. Richards and Cowland (1986) report on a careful instrumentation programme to measure water pressure in a series of sheeting joints.…”
Section: Hydrogeologymentioning
confidence: 99%
“…The paths may be tortuous and hard to identify and drainage measures can therefore be rather hit or miss (Hencher 2010). Regular patterns of long horizontal drain holes can be very effective, but it must never be expected that all drains will yield water flows and the effectiveness of individual drains can change with time as subsurface flow paths migrate.…”
Section: Drainagementioning
confidence: 99%